The changing relationship between racial identity and skin color in Brazil - Nicholas C. Freeman; Edward E. Telles; Rachel E. Goldberg (Proceedings of the National Academy of Sciences, 2025)
In recent years, Brazil’s non-White (Brown and Black) population became a numerical majority for the first time since the 19th century. Although we know this change was mostly due to racial reclassification, we do not know how such changes are related to skin color, the primary marker of race in Brazil. Using data from six Latin American Public Opinion Project (LAPOP), or America’s Barometer, surveys from 2010 to 2023, we examine how changes in racial self-identification (White, Brown, or Black) are related to respondent skin color (light, medium, or dark). We ask how the association between self-identified race and skin color changed over the 13-y period and to what extent these trends varied by educational level. We found a “darkening” of racial identification over time, especially among those with medium and dark skin, who increasingly identified as Black. Brazilians with light skin increasingly identified as Brown, but this was partly explained by changes in interviewer reporting of skin color in the same period. We found only minor evidence that education level was related to changing racial classification over time. Our findings further understanding of recent trends in racial reclassification, which may reflect growing Black consciousness and the extension of racial quotas to both Brown and Black Brazilians in federal universities and public sector jobs.